Multi-antigen MVA-vectored SARS-CoV-2 vaccine, GEO-CM04S1, induces cross-protective immune responses to ancestral and Omicron variants - Elsharkawy, Amany; Stone, Shannon; Guglani, Anchala; Wussow, Felix; Burleson, JD; Hauser, Mary; Domi, Arban; Kumari, Pratima; Albrecht, Todd R.; Dim, Chinonye; Newman, Mark; Diamond, Don J.; et al. (Frontiers in Immunology, 2025)
The design focus of the first-generation COVID-19 vaccines was on the use of the SARS-CoV-2 spike (S) protein as the primary vaccine immunogen to induce high levels of neutralizing antibodies. Efficacy was repeatedly disrupted due to the diminished neutralizing capacity of vaccine-induced antibodies against emerging variants. Vaccine candidate GEO-CM04S1 is based on the use of a modified vaccinia Ankara vector (MVA) that co-expresses S and nucleocapsid (N) antigens of the Wuhan-Hu-1 reference strain. It is designed to induce both antibody and T-cell responses to both S and N, with the goal of broadening immune response specificity and function. Herein, we characterized GEO-CM04S1 vaccine induced immune responses and efficacy against the ancestral Wuhan strain B.1 and the Omicron subvariant XBB.1.5 in K18-hACE-2 mouse model. We also tested experimental vaccine candidates that encode either S or N proteins alone and determined their relative levels and immunogenicity and contribution to efficacy. We demonstrated that immune responses induced by GEO-CM04S1 protects against weight loss, upper and lower respiratory tract infection, lung injury and excessive inflammation following intranasal challenge with B.1. We showed that only GEO-CM04S1 maintained full protective efficacy against the Omicron subvariant XBB.1.5. GEO-CM04S1 vaccination reduced viral replication without significant lung damage following XBB.1.5 infection. Despite full protection, no neutralizing antibodies were detected against XBB.1.5 in the sera of GEO-CM04S1-immunized animals, suggesting a critical role of T-cell responses. Using antibody-mediated depletion, we showed that depletion of CD20 cells or CD8+ T cells did not impact the vaccine protective efficacy whereas depletion of CD4+ T-cells diminished levels of efficacy. Collectively, our data demonstrate the full cross-variant protective immunity induced by GEO-CM04S1 and that CD4+ T-cell responses are a major effector element of vaccine protection.